Improving hearing assessment of children post-meningitis. Issue 11 (11th November 2003) - Wilson, C; Roberts, A; Stephens, D
Abstract : The improvement in audiological testing of children post-meningitis with one retrospective and two prospective audit cycles, is described. Direct referral by telephone prior to discharge and liaison with public health colleagues resulted in an increased assessment from 50% to 99% and 89% in successive audits. The proportion seen within six weeks also improved dramatically.